Puncak Prestasi Thariqah Mutakallimin Perspektif Pakhruddin ar-Razi - Nasiri Nasiri (Sekolah Tinggi Agama Islam Taruna Surabaya, 2020)
Fakhruddin ar-Razi is a great scholar who has mastered various branches of knowledge, especially Islamic sciences. In almost every branch of knowledge he studied, he wrote one or more works, some of which were the main references, such as the book al-Mahshul fi ʻIm al-Ushul and Tafsir al-Kabir Mafatih al-Ghaib. Even though he was a follower and defender of the Syafi'i school in the field of fiqh and Asy'ari in the field of kalam, his broad and deep mastery of knowledge and critical thinking about various sciences actually showed his capabilities as a mujtahid.His main work in the field of ushul fiqh, namely al-Mahshul, is the best work that collects four baboon books in the field of ushul fiqh thariqah mutakallimin from his predecessors. He succeeded in presenting ushul fiqh more comprehensively than had been done by his predecessors, including Imam asy-Shafi'i himself. Its analytical-critical descriptions provide depth of understanding of the various matters discussed in the book. Although his work is seen as the result of a merger of the four previous ushul fiqh books, his analyzes and some of his opinions show the independence and originality of the author's thoughts